STUDI PERJUMPAAN MISTISISME JAWA PERSPEKTIF AL-QUR’AN DAN MASYARAKAT MODERN - Asy'arie, Bima Fandi; Roibin, Roibin (FiTUA: Jurnal Studi Islam, 2024)
This study aims to explore the extent of Javanese mysticism from the perspective of al-Qur’an and modern society. The type used in this study is using a qualitative approach with literature (library research). Results in this study (1) The mystic of puppetry, which is likened to a poet, is found in QS. Asy-Syu’ara/26:222-22, (2) Mysticism “sastra dan gending,” which contains philosophical symbols and allegorical or better known from the work of Sultan Agung, (3) Mystical mirror, which is figurative or metaphorical in nature, where when one worships and faces Him specifically as self-introspection, contained in Q.S. al-Isra/17:23, (4) Mystical kebatinan, which leads to “Manunggaling Kawula Gusti,” which is defined as a union between “Kaula” and “God,” this is found in Q.S. al-An’am/6:162-163, (5) Magical mysticism, which examines a world that is difficult for human knowledge to reach. Overall, contemporary society has presented diverse perspectives in implementing and interpreting aspects of Javanese mysticism. While there are individuals who are more skeptical of the practice of mysticism, others still preserve their cultural heritage and may stick to the tradition.